Multifunctional MoO2-ICG nanoplatform for 808nm-mediated synergetic photodynamic/photothermal therapy. (June 2019) - Fang, Chao; Yan, Peijian; Ren, Zhaohui; Wang, Yifan; Cai, Xiujun; Li, Xiang; Han, Gaorong
Graphical abstract: Highlights: First time to endow MoO2 nanoparticles with capability of ROS production by ICG. ROS production is remarkably enhanced within cancer. PTT and PDT are induced synchronously by a single NIR light. Abstract: A variety of approaches have been investigated in the development of photothermal (PTT) and photodynamic (PDT) therapies for cancer treatment. However, when used in isolation, both PTT and PDT suffer from intrinsic drawbacks, resulting in unsatisfactory therapeutic efficacy. We describe here, a multifunctional nanoplatform, enabling the effective combination of PTT and PDT, triggered by a single 808nm-NIR light. This platform is based on MoO2 nanoparticles, which can effectively transform NIR light into heat. By attaching molecules of indocyanine green (ICG), a hydrophilic and biocompatible NIR-mediated photosensitizer, to the surface of the particles, both photothermal and photodynamic effects can be achieved. Using an in vitro study with 4T1 cancer cells, we have demonstrated that irradiating the particles with 808nm NIR can trigger ROS production and create heat within cells. Both mechanisms acting synchronously are likely to result in superior in vivo efficacy in tumor phototherapy.